Development of a microsurgery‐assisted robot for high‐precision thread traction and tension control, and confirmation of its applicability. Issue 2 (1st December 2020) - Hangai, Satoshi; Nozaki, Takahiro; Soma, Tomoya; Miyashita, Hidetaka; Asoda, Seiji; Yazawa, Masaki; Sato, Kazuki; Kawana, Hiromasa; Ohnishi, Kouhei; Kobayashi, Eiji
Abstract: Background: Microsurgery requires high skills for suturing using fragile threads, often within narrow surgical fields. Precise tension is required for good healing and to avoid the risk of thread breakage. Methods: To meet the demands, we developed a novel assist robot utilizing high‐precision sensorless haptic technology. The robot adopts a cable‐driven mechanism to maintain a distance from the surgical area and enhances compatibility with surgical equipment such as microscopes. The robot performance was verified through in vitro and in vivo experiments using a rat model. Results: The realization of precise tension control was confirmed in both experiments. In particular, in the in vivo experiments, the developed robot succeeded to produce a knot with an accurate tension of 0.66% error. Conclusions: The developed robot can realize to control traction force precisely. This technology might open up the window for a full assist robot for microsurgery with haptic feeling.